Burnout of intrinsically motivated GPs when exposed to external regulation: A combined panel data survey and cluster randomized field experiment. Issue 4 (April 2021) - Pedersen, Line Bjørnskov; Hvidt, Elisabeth Assing; Waldorff, Frans Boch; Andersen, Merethe Kousgaard
Highlights: GPs with high intrinsic motivation are less burned out than their colleagues. The intrinsically motivated GPs are more burned out when exposed to accreditation. Intrinsic motivation may not shield from burnout when external regulation is imposed. Policy makers are encouraged to carefully design new external regulation systems. Abstract: Burnout among general practitioners (GPs) is a problem in many countries. Research indicates that burnout is less likely to occur among intrinsically motivated employees. Based on self-determination theory, we investigate 1) whether intrinsically motivated GPs are less burned out than their colleagues, and 2) whether the most intrinsically motivated GPs are more likely to burn out when exposed to an external regulatory accreditation programme. General practices in Denmark were cluster randomized to mandatory accreditation in 2016, 2017 or 2018. We measure GPs' intrinsic motivation and burnout levels one and two years into the accreditation process. We use a balanced panel of GPs (n = 846) to estimate mixed effects ordered logit models. We find that GPs with high intrinsic motivation are less burned out than their colleagues. However, the most intrinsically motivated GPs are significantly more burned out when exposed to accreditation compared to their colleagues. We conclude that being intrinsically motivated may not shield from burnout when external regulation is imposed.